Molecular typing revealed the emergence of pvl-positive sequence type 22 methicillin-susceptible Staphylococcus aureus in Urumqi, Northwestern China - Yuan W; Liu J; Zhan Y; Wang L; Jiang Y; Zhang Y; Sun N; Hou N (Infection and Drug Resistance, 2019)
Wenchang Yuan,1,2,* Jianhua Liu,2,3,* Youchao Zhan,1,* Li Wang,2 Yanqiong Jiang,1 Yanling Zhang,1 Ning Sun,1,4 Ning Hou1,51Department of Clinical Laboratory, The Fifth Affiliated Hospital of Guangzhou Medical University, Guangzhou, 510700, People’s Republic of China; 2Department of Clinical Laboratory, General Hospital of Xinjiang Military Region, Urumqi 830001, People’s Republic of China; 3Department of Intensive Care Unit, the Fourth Hospital of Changsha, Changsha 410006, People’s Republic of China; 4State Key Laboratory of Chemical Biology and Drug Discovery, and Department of Applied Biology and Chemical Technology, The Hong Kong Polytechnic University, Hung Hom, Kowloon, Hong Kong, People’s Republic of China; 5School of Pharmaceutical Sciences, Guangzhou Medical University, Guangzhou 511436, People’s Republic of China*These authors contributed equally to this work Background: Staphylococcus aureus is among the most common causes of health care- and community-associated infections worldwide. The distributions of different S. aureus clones change over time and also vary geographically. The purpose of this study was to determine the molecular type and antimicrobial resistance profiles of clinical S. aureus strains isolated in Urumqi, Northwestern China.Methods: A total of 605 clinical S. aureus isolates were collected from Xinjiang Military General Hospital, in Urumqi. Protein A-encoding (spa) typing, multilocus sequence typing, staphylococcal chromosomal cassette mec typing, Panton-Valentine leucocidin (pvl) gene detection, and antimicrobial resistance profiling were performed.Results: Among these strains, 271 isolates (44.7%) were methicillin-resistant S. aureus (MRSA) and 334 (55.3%) were methicillin-susceptible S. aureus (MSSA). The MRSA strains consisted of 22 spa types and 14 sequence types (STs). ST239-MRSA-III-t030 (73.1%, 198/271) and ST59-MRSA-IV-t437 (11.8%, 32/271) were the most common, and ST22-MRSA-IV-t309 was the rarest (2.02%, 6/271). The MSSA strains consisted of 93 spa types and 29 STs. ST22, ST121, ST398, ST5, ST7, ST188, and ST15 were the main MSSA STs, and ST22-MSSA-t309 was most common (26.0%, 87/334). The pvl gene was present in 20.3% of all S.aureus strains, and 80.8% (88/99) of ST22-MSSA strains harbored the pvl gene. A total of 85.7% pvl-positive ST22-MSSA strains were spa t309 (85/99), and 87.5% of pvl-positive ST22-MSSA strains were from abscesses or wounds (skin and soft tissue infections). All ST239-MRSA strains were resistant to gentamicin (GEN), levofloxacin (LEV), ciprofloxacin (CIP), moxifloxacin (MXF), rifampicin (RIF), and tetracycline (TET). Among the ST59-MRSA strains, over 70.0% were resistant to erythromycin (ERY), clindamycin (CLI), and TET. ST22-MSSA remained susceptible to most antibiotics, but was resistant to PEN (97.0%), ERY (57.6%), and CLI (15.2%).Conclusion: Our major results indicated that the antimicrobial resistance profiles and pvl genes of S. aureus isolates from Urumqi were closely associated with clonal lineage. ST239-MRSA-III-t030 and pvl-positive ST22-MSSA-t309 were the most common clones in this region of Northwestern China.Keywords: Staphylococcus aureus, methicillin-sensitive Staphylococcus aureus, methicillin-resistant Staphylococcus aureus, pvl gene, molecular typing